Protective effect of cinnamon against cadmium-induced hepatorenal oxidative damage in rats - Abdeen, Ahmed; Ghonim, Ahmed; El-Shawarby, Ragab; Abdel-Aleem, Nabila; El-Shewy, Elham; Abdo, Mohamed; Abdelhiee, Ehab (International Journal of Pharmacology and Toxicology, 2017)
Background: Cadmium (Cd) is a well-known hazardous environmental contaminant. It exerts its toxicity through induction of lipid peroxidation and reduction of cellular antioxidant. Therefore, in this study, we investigated whether cinnamon could protect against Cd toxicity in liver and kidney.Materials and methods: Forty male Wister rats (130-135 gm) were divided randomly into 4 groups/ 10 rats each. Control, cinnamon, cadmium, and Cinn+Cd groups received distilled water, cinnamon extract (200 mg/kg b.wt. orally), cadmium chloride (5 mg/kg b.wt. orally), and Cd plus cinnamon, respectively. Blood, liver, and kidney samples were collected after 8 weeks of treatment. Erythrogram, leukogram, liver and kidney functions, and oxidative status (MDA, CAT, and TAC) were determined.Results and discussion: Cd-treated animals showed significant increases in serum ALT, AST, creatinine, and urea indicating hepatic and renal damage. Cd-induced oxidative stress was observed by marked decease TAC accompanied by increase in MDA which contributed in liver and kidney dysfunction. Co-treatment of Cd with cinnamon has improved the oxidation profile by increasing the TAC and decreasing the lipid peroxidation. Cinnamon ameliorated the toxic effect of Cd, which observed by improvement of liver and kidney functions.Conclusion:Â High antioxidants content of cinnamon could protect the liver and kidney from Cd toxicity.Â